Ulipristal acetate versus gonadotropin-releasing hormone agonists prior to laparoscopic myomectomy (MYOMEX trial): Long term results of a double-blind randomized controlled trial. (September 2020) - De Milliano, Inge; Middelkoop, Mei-An; Huirne, Judith A.F.; Kwee, Janet; Geomini, Peggy M.A.J.; Schoot, Benedictus C.; Van Baal, Marchien; Bosmans, Judith E.; Hehenkamp, Wouter J.K.
Abstract: Objective: The aim of this study was to compare the effect of ulipristal acetate (UPA) and gonadotropin-releasing hormone agonists (GnRHa) before laparoscopic myomectomy on long term secondary outcomes of the MYOMEX-trial, regarding quality of life, ultrasound characteristics, hemoglobin levels 6 weeks post-operative, sexual function and menstrual bleeding control. A cost-analysis was also performed. Short-term primary and secondary outcomes are reported elsewhere. Study design: A double-blind, randomized, controlled, non-inferiority trial in nine hospitals in the Netherlands. Participants were randomized in a 1:1 ratio (block size of four, stratified per hospital) to either UPA or GnRHa pre-treatment. Additional placebo injections containing saline, respectively daily placebo tablets were given to both groups to ensure double-blinding. Surgery was performed within a month after the last tablet. Women were followed up until six months post-surgery. Results: A total of 55 participants were randomized: 30 to the UPA- and 25 to the GnRHa-group between May 2015 and July 2017. Uterine volume at six weeks post-operative did not differ significantly between both pre-treatment groups with 170.1 cm 3 (106.8–243.5; N = 29) vs. 152.8 cm 3 (92.3–205.6; N = 23) for the UPA- and GnRHa-group respectively (p = 0.423). Hemoglobin levels six weeks post-operatively recovered back to baseline and were not significantly different between groups with 7.7 mmol/L for the UPA- vs. 8.1 mmol/L for the GnRHa-group (p = 0.157; mean difference -0.4 (CI -0.9, 0.2). Menstrual bleeding pattern, quality of life, effects on general and sexual health showed a significant improvement compared to baseline in both groups without any differences between the treatment groups. Symptom severity scores also decreased significantly at 6 week post-operatively compared to baseline, but did not differ between the treatment groups. Fibroid characteristics at baseline (e.g. mean diameter of largest fibroid) appeared not to be a confounding factor. An exploratory cost analysis showed no significant differences in absenteeism costs, total healthcare and societal costs, after adjustment for confounding factors. Conclusion: Pre-treatment prior to laparoscopic myomectomy with UPA compared to GnRHa has similar effects on bleeding pattern, menopausal symptoms, sexual functioning, symptom severity and quality of life from baseline up to six months post-operative. Due to the small sample size, these findings should be interpreted with caution. Also, no firm conclusions on costs could be made.